Nintedanib with add-on pirfenidone in idiopathic pulmonary fibrosis: results of the INJOURNEY Trial - Vancheri, Carlo; Kreuter, Michael; Richeldi, Luca; Ryerson, Christopher J.; Valeyre, Dominique; Grutters, Jan C.; Wiebe, Sabrina; Stansen, Wibke; Quaresma, Manuel; Stowasser, Susanne; Wuyts, Wim A. (American journal of respiratory and critical care medicine, 2018)
Rationale: Nintedanib and pirfenidone slow the progression of idiopathic pulmonary fibrosis (IPF), but the disease continues to progress. More data are needed on the safety and efficacy of combination therapy with nintedanib and add-on pirfenidone.Objectives: To investigate safety, tolerability, and pharmacokinetic and exploratory efficacy endpoints in patients treated with nintedanib and add-on pirfenidone versus nintedanib alone.Methods: Patients with IPF and FVC greater than or equal to 50% predicted at screening who completed a 4- to 5-week run-in with nintedanib 150 mg twice daily without dose reduction or treatment interruption were randomized to receive nintedanib 150 mg twice daily with add-on pirfenidone (titrated to 801 mg three times daily) or nintedanib 150 mg twice daily alone in an open-label manner for 12 weeks. The primary endpoint was the percentage of patients with on-treatment gastrointestinal adverse events from baseline to Week 12. Analyses were descriptive and exploratory.Measurements and Main Results: On-treatment gastrointestinal adverse events were reported in 37 of 53 patients (69.8%) treated with nintedanib with add-on pirfenidone and 27 of 51 patients (52.9%) treated with nintedanib alone. Predose plasma trough concentrations of nintedanib were similar when it was administered alone or with add-on pirfenidone. Mean (SE) changes from baseline in FVC at Week 12 were −13.3 (17.4) ml and −40.9 (31.4) ml in patients treated with nintedanib with add-on pirfenidone (n = 48) and nintedanib alone (n = 44), respectively.Conclusions: Nintedanib with add-on pirfenidone had a manageable safety and tolerability profile in patients with IPF, in line with the adverse event profiles of each drug. These data support further research into combination regimens in the treatment of IPF.Clinical trial registered with www.clinicaltrials.gov (NCT02579603).